PENERAPAN MODEL PEMBELAJARAN SAINS TEKNOLOGI DAN MASYARAKAT(STM) TERHADAP KEMAMPUAN KETERAMPILAN PROSES SAINS SISWA PADA KONSEP PENCEMARAN LINGKUNGAN DI SMA NEGERI 1 DARMA - Nikeu Angraeni; Anna Fitri Hindriana; Haruji Satianugraha (Program Studi Pendidikan Biologi, FKIP Universitas Kuningan, 2015)
The Background of the research is low ability students in problem solving science process skills. The purpose of this study was to determine the application of the science learning technology and society in the ability of science process skills. This study used quantitative methods with design pre-experimental of the One-Shot Case Study. To obtain the necessary data, used instruments test questionnaire as the main data. Questionnaire was supporting data collection determine the response of student. The population was all students in class X SMAN 1 Darma second semester of school year 2013/2014 as many as 190 people. Samples 73 used from two classes, namely class X3 and X4, sampling is done by cluster random sampling technique. the hypothesis Testing in this study using descriptive statistics test and parametric statistical tests. Based on the results of the analysis showed that the ability of science process skills class X when the learning is good withan average of 83.68%. Indicator of the ability of science process skills that have the greatest percentage of 90.75% observed was with both the category and the smallest percentage gain is the interpretation of the indicator by 78.76%. Hypothesis testing using parametric statistical tests in this case using the Z test to determine the application of the learning model of science technology and society of the ability of science process skills, from data analysis of data obtained from average of 7.65, obtained that ZhitungZtabel yaitu 7.652,33. And to test the proportion of data obtained ZhitungZtable1 7,762.33. This means that themodel of science technology and society influence the ability of science process skills. 89.66% of students responded positively dan10, 34% gave a negative response to the model of science technology and society.Keywords: learning model of science technology and society, science process skills, environmental pollution